2020
DOI: 10.4078/jrd.2020.27.4.261
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profiles in Anti-neutrophil Cytoplasmic Antibody-associated Vasculitis: A Cross-sectional Analysis

Abstract: Objective. Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is an autoimmune disease (AID) characterised by necrotising intravascular inflammation. Growing evidence suggests that immune system triggers altered lipid metabolism in AIDs. We investigated whether changes in lipid profile correlate with severity of disease in AAV. Methods. Seven lipid profiles were evaluated utilizing frozen serum samples from 67 patients registered in the Severance Hospital ANCA-associated VasculitidEs cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Patient inclusion. We utilized serum samples and data from 79 patients who were included in the Severance Hospital ANCAassociated VasculitidEs (SHAVE) cohort, which is an observational registry of patients with AAV established at Severance Hospital, Republic of Korea (14). Patients were classified into AAV subtypes according to the 2007 European Medicines Agency algorithm (15) and the 2012 revised International Chapel Hill Consensus Conference Nomenclature of Vasculitides (16).…”
Section: Methodsmentioning
confidence: 99%
“…Patient inclusion. We utilized serum samples and data from 79 patients who were included in the Severance Hospital ANCAassociated VasculitidEs (SHAVE) cohort, which is an observational registry of patients with AAV established at Severance Hospital, Republic of Korea (14). Patients were classified into AAV subtypes according to the 2007 European Medicines Agency algorithm (15) and the 2012 revised International Chapel Hill Consensus Conference Nomenclature of Vasculitides (16).…”
Section: Methodsmentioning
confidence: 99%
“…It also implies that lipid profile decreases in active disease state with active inflammation which is consistent with findings in other inflammatory rheumatic diseases. Ahn et al [18] also demonstrated relationship between lipid profile and disease activity in AAV in a cross-sectional study. It was irrespective of treatment of corticosteroids and immunosuppressant and apolipoprotein A1 (apoA1) showed the most significant correlation.…”
mentioning
confidence: 86%
“…Ahn et al [ 18 ] also demonstrated relationship between lipid profile and disease activity in AAV in a cross-sectional study. It was irrespective of treatment of corticosteroids and immunosuppressant and apolipoprotein A1 (apoA1) showed the most significant correlation.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…The primary limitation of this study was that the sample size was not large enough to sufficiently represent all Korean patients with AAV, and the study was retrospectively conducted. Owing to the small number of patients with ACS, the subgroup analysis on the effects of the traditional risks for ACS such as hypertension, DM, CKD, and dyslipidaemia on ACS occurrence in AAV patients could not be performed [37], and in particular, the baseline high-sensitive CRP levels, which are associated with ACS more closely than CRP levels, could not be collected owing to the retrospective study design [38]. However, because the same three rheuma-…”
Section: At Diagnosismentioning
confidence: 99%